Strategic ignorance and perceived control - Balietti, Anca; Budjan, Angelika J.; Eymess, Tillmann; Soldà, Alice (AWI discussion paper series, 2023)
Information can trigger unpleasant emotions. As a result, individuals might be tempted to willfully ignore it. We experimentally investigate whether increasing perceived control can mitigate strategic ignorance. Participants from India were presented with a choice to receive information about the health risk associated with air pollution and later asked to recall it. We find that perceived control leads to a substantial improvement in information retention. Moreover, perceived control mostly benefits optimists, who show both a reduction in information avoidance and an increase in information retention. This latter result is confirmed with a US sample. A theoretical framework rationalizes these findings.